2021
DOI: 10.1111/ped.14521
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease presenting with hoarseness: A multinational study of the REKAMLATINA network

Abstract: Background Recently, hoarseness affecting the supraglottic structure has been reported in Kawasaki disease (KD). The objective of this study was to characterize the frequency of hoarseness in acute KD patients in Latin America. Methods We used prospective data from the multinational Red de Enfermedad de Kawasaki en America Latina (REKAMLATINA) network. A total of 865 patients from 20 countries were enrolled during the 3 year study period. Data on hoarseness were available in 858 (99.2%) patients. The clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, there was no significant group difference, which was probably related to the small sample size. Previous studies revealed that hoarseness was found to be prevalent as a presenting sign of acute KD in younger children, it might be related to viral infection and immunological diseases, and hoarseness was presented in 11.6–30.0% patients [ 21 , 22 ]. However, in children with retropharyngeal abscess, hoarseness often be caused by compression of nerves by abscesses or inflammatory edema in the glottic region, the incidence of hoarseness was relatively low [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no significant group difference, which was probably related to the small sample size. Previous studies revealed that hoarseness was found to be prevalent as a presenting sign of acute KD in younger children, it might be related to viral infection and immunological diseases, and hoarseness was presented in 11.6–30.0% patients [ 21 , 22 ]. However, in children with retropharyngeal abscess, hoarseness often be caused by compression of nerves by abscesses or inflammatory edema in the glottic region, the incidence of hoarseness was relatively low [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguing aspects of Kawasaki disease epidemiology include the distinct global seasonality, with peaks in winter, spring and mid-summer, and the temporal and spatial clustering of cases 91 94 . No evidence exists to support person-to-person transmission of Kawasaki disease, and clinical features, including cervical lymphadenopathy, hoarseness and retropharyngeal oedema, all suggest a respiratory point of entry 95 97 . Potential clues to the aetiology of Kawasaki disease can be gleaned from the analysis of temporal clusters that share distinct clinical and laboratory features.…”
Section: Medium Vessel Vasculitismentioning
confidence: 99%